Genome-wide microRNA expression profiling in placentas of fetuses with Down syndrome. Issue 3 (March 2015) - Lim, J.H.; Kim, D.J.; Lee, D.E.; Han, J.Y.; Chung, J.H.; Ahn, H.K.; Lee, S.W.; Lim, D.H.; Lee, Y.S.; Park, S.Y.; Ryu, H.M.
Abstract Introduction Down syndrome (DS) is the most common aneuploidy, caused by an extra copy of all or part of chromosome 21 (chr21). Differential microRNA (miRNA) expression is involved in many human diseases including DS. However, the genome-wide changes in miRNA expression in DS fetal placentas have yet to be determined, and the function of these changes is also unclear. Methods We profiled genome-wide miRNA expression in placenta samples from euploid or DS fetuses by using microarray technology and predicted the functions of differentially expressed miRNAs using bioinformatics tools. Results Thirty-four miRNAs were significantly differentially expressed in the DS placenta compared with the normal placenta (16 up-regulated and 18 down-regulated). However, expression of chr21-derived miRNAs did not change. Predicted target genes included 7434 genes targeted by up-regulated miRNAs and 6071 genes targeted by down-regulated miRNAs. Seventy-six of these target genes were located on chr21 (10 genes controlled by down-regulated miRNAs and 34 genes by up-regulated miRNAs, and 32 genes by both). Target genes on chr21 were significantly associated with DS and DS-related disorders, such as mental retardation, neurobehavioral manifestations, and congenital abnormalities. Discussion To our knowledge, this is the first genome-wide study to comprehensively survey placental miRNAs in DS fetuses. Our results provide new insight into miRNA expression in placentas of fetuses with DS. Additionally, our findings indicate that the differentially expressed miRNAs in the DS placenta may potentially affect various pathways related to DS pathogenesis.